Maleic acid and EDTA mediated extenuation of Co(II) stress in Hordeum vulgare seedlings. Issue 2 (July 2019) - Mahey, Sonia; Kumar, Rakesh; Kumar, Vinod; Sharma, Resham; Sharma, Manik; Bhardwaj, Renu; Thukral, A.K.
Abstract: The present study was performed to assess the effects of maleic acid (MA), ethylenediaminetetraacetic acid (EDTA) amendments on biochemical parameters of 7 days old seedlings of Hordeum vulgare L. under Co(II) stress. Application of MA, EDTA, Co(II) alone significantly reduced the root length and shoot length, whereas combination of MA and Co(II), and EDTA and Co(II) enhances the root and shoot length. The antioxidative enzymes such as superoxide dismutase, catalase, guaiacol peroxidase, ascorbate peroxidase and glutathione reductase were significantly enhanced under application of MA, EDTA, Co(II) alone, while their combinations reduced the activities of all the antioxidative enzymes. Multivariate regression analysis and β-regression coefficients showed that β1 (Co) and β2 (MA) have positive regression on the antioxdative enzymes, while β3 (Co × MA) have negative regression with the antioxidative enzymes. Similarly, β1 (Co) and β2 (EDTA), and β3 (Co × EDTA) showed the similar trend as that of Co and MA. Malondialdehyde (MDA) content is increased under Co stress, whereas MA and EDTA alone or in combination with Co reduce the MDA content. Multiple linear regression analysis also showed that MDA content is significantly enhanced under β1 (Co) stress, whereas in combination with MA or EDTA decreases the MDA content.